PERAN PEMERINTAH DALAM PENGENDALIAN PERTUMBUHAN PENDUDUK DI KOTA PEKANBARU TAHUN 2019 - Ayuri, Dhea (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
According to Law Number 52 of 2009 concerning Population Development and Family Development, population is matters related to the number, structure, growth, distribution, mobility, distribution, quality, and welfare conditions relating to politics, economy, socio-culture, religion and neighborhood of the local population. The formulation of the problem in this study is how the role of government in controlling population in Pekanbaru City, what are the factors that influence the government in controlling population in Pekanbaru City and whether the government is very helpful in controlling population in Pekanbaru City.This study aims to determine the role of the government in solving population control problems in Pekanbaru City. In addition, this study uses a qualitative approach and data collection techniques are observations (observations), interviews (interviews) and documentation.The result of this research is that the role of Pekanbaru City government through Disdalduk KB is already good, because the programs run by Disdalduk KB have been able to suppress population growth that occurs in Pekanbaru which does not reach three (3) percent a year. Implementation carried out by Disdalduk KB in this case is hampered by a pandemic that is felt almost all over the world, counseling is the spearhead of Disdalduk KB in the delivery of national programs, and these obstacles are also related to doctors and midwives who reduce patients during this pandemic. The role of the government in suppressing the rate of population growth is quite good, it can be seen from the population spike which in general our society does not have many children because of the programs carried out by the government.Keywords: Role of Government, Control, Population and City Growth Pekanbar